The Effectiveness of Compensation in Improving Employee Motivation, Discipline, and Performance - Abdul Rochman; Sutianingsih (Indonesian Journal of Business Analytics, 2025)
The purpose of this study is to find out how compensation for work motivation, work discipline and employee performance. Specifically, this study investigated the extent to which compensation affects employee work motivation, work discipline and performance. The type of data used is quantitative data, while the source of research data is primary data, namely data collected directly by the researcher through the provision of questionnaires. The analysis method in this study uses path analysis. Data processing using SmartPLS. The study's findings demonstrate that pay rates significantly impact workers' levels of motivation, discipline, and output. Employee performance is positively and significantly impacted by work motivation and discipline. The compensation route test shows that it indirectly affects performance in a favorable and statistically significant way via encouraging and enforcing discipline in the workplace.